An evaluation of the impact of aggressive hypertension, diabetes and smoking cessation management on CVD outcomes at the population level: a dynamic simulation analysis - John Pastor Ansah; Ryan Leung Hoe Inn; Salman Ahmad (BMC, 2019)
Abstract Background Evidence from randomized control trials suggest that coupled with smoking cessation interventions, CVD events can be reduced significantly if hypertension and diabetes patients are properly managed, raising practical what-if questions at the population level. This research aims to develop a dynamic simulation model using the systems modelling methodology of system dynamics, to evaluate the medium to long-term impact of hypertension and diabetes management, as well as smoking cessation intervention on CVD events, CVD deaths and post-CVD population. Methods The systems modelling methodology of system dynamics was used to develop a simulation model to evaluate the impact of aggressive hypertension, diabetes and smoking cessation management on CVD outcomes at the population level. Result The insights from this research suggest that despite that at the individual level, hypertension management is associated with the highest risk reduction for CVD (50%) compared to diabetes and smoking (20%) and is also the most prevalent risk factor, at the population level, diabetes management interventions are projected to have higher impact on reducing CVD events compared to hypertension management or smoking cessation interventions. However, a combined intervention of diabetes and hypertension management, as well as smoking cessation has the most impact on CVD outcomes. Conclusion Due to aging population and the increasing prevalence of chronic conditions in Singapore, the number of CVD events in Singapore is projected to rise significantly in the near future-hence the need for proactive planning to implement needed interventions. Findings from this research suggest that CVD events and its associated deaths and disabilities could be reduced significantly if diabetes and hypertension patients are aggressively managed.